METAKOGNISI : ADAKAH PERBEDAAN SISWA MELANKOLIS DAN KOLERIS ? - Dani Hanifatuzzahra; Harina Fitriyani (Jurnal Numeracy, 2021)
This study aims to obtain an overview of the characteristics and levels of metacognitive ability of junior high school students as seen from the melancholic and choleric personality types according to Hippocrates-Galenus. The results of this study are expected to be used as consideration for teachers in designing mathematics lessons that pay attention to personality types and students' metacognitive processes. A qualitative descriptive approach was chosen to answer the research objectives. At the same time, the research subjects were two grade VII students with melancholic and choleric personality types in one of the Muhammadiyah Junior High Schools in Jepara. The purposive sampling technique used in this research to subject selection. Data collection techniques used personality type questionnaires, metacognition tests, and interviews. Data analysis used three steps, namely data reduction, data presentation and conclusion drawing. The results showed that melancholic and choleric students had different characteristics and levels of metacognition. Melancholic students are at the metacognitive level between tacit use and aware use, while the rest of the cholerics are at the tacit use metacognition level. Penelitian ini bertujuan untuk mendapatkan gambaran tentang karakteristik dan jenjang kemampuan metakognisi siswa SMP yang dilihat dari tipe kepribadian melankolis dan koleris menurut Hippocrates-Galenus. Hasil penelitian ini diharapkan dapat dijadikan sebagai bahan pertimbangan guru dalam mendesain pembelajaran matematika yang memperhatikan tipe kepribadian dan proses metakognisi siswa. Pendekatan deskriptif kualitatif dipilih untuk menjawab tujuan penelitian. Sedangkan subjek penelitian adalah dua orang siswa kelas VII yang bertipe kepribadian melankolis dan koleris di salah satu SMP Muhammadiyah di Jepara. Adapun teknik pemilihan subjek penelitian menggunakan teknik purposive sampling. Teknik pengumpulan data menggunakan angket tipe kepribadian, tes metakognisi, dan wawancara. Analisis data menggunakan tiga langkah yakni reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa melankolis dan koleris memiliki karakteristik dan jenjang metakognisi berbeda. Siswa melankolis berada pada jenjang metakognisi antara tacit use dan aware use, sedangkan sisa koleris berada pada jenjang metakognisi tacit use. Kata Kunci: Metakognisi, Melankolis, Koleris, Jenjang Metakognisi